2001
DOI: 10.1530/rep.0.1210863
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in reproductive hormones and conceptus-endometrial interactions during embryonic diapause and reactivation of the blastocyst in European roe deer (Capreolus capreolus)

Abstract: The roe deer blastocyst is in diapause between August and December, after which time it expands and elongates rapidly before implantation. Blood samples were taken from 30 animals to define temporal changes in reproductively important hormones to investigate the physiological cues present at embryo reactivation. In 15 of these animals, changes in uterine and conceptus protein synthesis and secretion, and luteal progesterone release during diapause and reactivation, were assessed after culture of these tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 8 publications
4
18
1
Order By: Relevance
“…Support for the former view can be found in studies that have shown increases in protein synthesis and secretion coinciding with the termination of diapause in roe deer (Lambert et al 2001) and carnivores (Mead 1989). In the mare, it is known that uterine secretions vary in a stage-dependent manner related to the duration of either endogenous or exogenous progesterone (Zavy et al 1982, Hinrichs et al 1989, and it is reasonable to assume that some of these proteins play a role in promoting embryonic development, particularly in view of the increased incidence of early pregnancy failure in older mares suffering fibrotic degenerative changes in the endometrium, which render the secretory glands non-functional (Stewart et al 1998, Morris & Allen 2002, Allen et al 2007.…”
Section: Discussionmentioning
confidence: 88%
“…Support for the former view can be found in studies that have shown increases in protein synthesis and secretion coinciding with the termination of diapause in roe deer (Lambert et al 2001) and carnivores (Mead 1989). In the mare, it is known that uterine secretions vary in a stage-dependent manner related to the duration of either endogenous or exogenous progesterone (Zavy et al 1982, Hinrichs et al 1989, and it is reasonable to assume that some of these proteins play a role in promoting embryonic development, particularly in view of the increased incidence of early pregnancy failure in older mares suffering fibrotic degenerative changes in the endometrium, which render the secretory glands non-functional (Stewart et al 1998, Morris & Allen 2002, Allen et al 2007.…”
Section: Discussionmentioning
confidence: 88%
“…As a consequence, it helps the species survive extreme forms of stress (e.g., drought) and it also “times” the birth of offspring to a more favorable environment (e.g., rainy season). In nature, diapause phenomena are widespread throughout the animal kingdom, from simple organisms such as brine shrimps and silkworms, to mammals such as the roe deer, bats, and mice (Bleier, 1975; Emerson, Bradshaw & Holzapfel, 2009; Hand, Denlinger, Podrabsky & Roy, 2016; Lambert et al., 2001; Lopes, Desmarais & Murphy, 2004; Meenakumari & Krishna, 2005; Ptak et al., 2012; Sato et al., 2014; Schiesari & O'Connor, 2013; Sim & Denlinger, 2013). Our current knowledge of diapause has benefited greatly from the studies in invertebrates.…”
Section: Using the African Turquoise Killifish As A Research Organismmentioning
confidence: 99%
“…At this stage it is attached to the placenta. Various factors could be associated with the reactivation of the roe deer blastocyst from diapause including environmental cues, changes in the profile of maternal hormones or secretion of biochemical signals by the endometrium or conceptus (Lambert et al, 2001). Embryonic diapause exists in numerous mammals, such as some mustelids (Mustelidae) and seals (Pinnipedia), but the roe deer is the only artiodactyl known to use embryonic diapause as a reproductive strategy (Andersen et al, 1998).…”
Section: Razmnoževalni Potencial Srnjadimentioning
confidence: 99%